Pternopetalum shunhuangensis (Apiaceae), a new species from Hunan, China - Wei Zhou; Zi-Lin Feng; Long-Ping Tang; Du Deng; Bao-cheng Wu; Lei Wu (PhytoKeys)
Based on field investigations, morphological and molecular systematic studies, a new species, Pternopetalum shunhuangensis (Apiaceae) from Hunan Province, China is described. Diagnostic morphological characters, full description and a detailed illustration are provided. The differences between P. shunhuangensis and morphologically similar species P. tanakae are presented and discussed. Since no population assessment of this species in its whole distribution area is made, it is best to assign a conservation status of ‘Data Deficient’ (DD) for this species.